Contando nos dedos: aprendizagem e desenvolvimento numérico - Cunha, Élison Rixadson Araújo (2019)
This study aimed to investigate the effectiveness of a finger-counting stimulation program for the development of mathematical skills. Two articulated studies were carried out in order to answer the research questions. The first one aimed to adapt the instructional material developed in Germany, establishing the canonical pattern of finger-counting among children from the city of Natal / RN / Brazil. One-hundred university students from this city, 50 women and 50 men, participated in this study. They performed two tasks, namely laterality and ordinality. Results pointed out the existence of canonical pattern of counting with the fingers in Natal / RN / Brazil. The second study investigated the effectiveness of the finger-stimulation program in counting on the development of mathematical skills. This was a predominantly quantitative quasi-experimental prospective and interventive longitudinal study. The sample of participants was formed by 40 children of both sexes, with ages varying from 6 to 7 years. They were 1 st year elementary school I students from two regular classes from a public school in the city of Natal-RN. One class (experimental group) was submitted to the 18-week fingertip stimulation program. The second group (control group) carried out the activities planned by the school. The general, somatosensory and mathematical cognitive abilities of both classes were assessed by the beginning and by the end of the 18 weeks period. There was no statistical significant difference between the two groups in the pre-test evaluation. However, in the post-test, significant differences were identified between the classes, in favor of the experimental group, in addition skills, digital gnosia, numerical magnitude and representation. These results allowed to identify the effectiveness of the program, which on the other hand will support effective interventions and public policies aimed to minimize school difficulties in mathematics identified among Brazilian children in national and international assessment instruments.